2008
DOI: 10.1021/la800334k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization Enhanced Nuclear Magnetic Resonance and Electron Spin Resonance Studies of Hydration and Local Water Dynamics in Micelle and Vesicle Assemblies

Abstract: We present a unique analysis tool for the selective detection of local water inside soft molecular assemblies (hydrophobic cores, vesicular bilayers, and micellar structures) suspended in bulk water. Through the use of dynamic nuclear polarization (DNP), the (1)H NMR signal of water is amplified, as it interacts with stable radicals that possess approximately 658 times higher spin polarization. We utilized stable nitroxide radicals covalently attached along the hydrophobic tail of stearic acid molecules that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 65 publications
0
47
0
Order By: Relevance
“…The coupling factor strongly depends on the translational correlation time, s t , between the radical and nucleus of interest. The coupling factor decreases with increasing correlation times [1,18], and previous reports have shown that the dipolar interaction for water [19] and small organic molecules [16] with organic radicals is modulated mainly by translational motion, which leads us to discuss our results in terms of translational instead of rotational correlation. The translational correlation time is a function of the distance of closest approach, d, between the nucleus and radical and their respective diffusion coefficients, D I and D S [1]:…”
Section: Theorymentioning
confidence: 56%
“…The coupling factor strongly depends on the translational correlation time, s t , between the radical and nucleus of interest. The coupling factor decreases with increasing correlation times [1,18], and previous reports have shown that the dipolar interaction for water [19] and small organic molecules [16] with organic radicals is modulated mainly by translational motion, which leads us to discuss our results in terms of translational instead of rotational correlation. The translational correlation time is a function of the distance of closest approach, d, between the nucleus and radical and their respective diffusion coefficients, D I and D S [1]:…”
Section: Theorymentioning
confidence: 56%
“…At [oleic acid + oleate] = 25 mM and above pH 10, both lipophilic TEMPO-spin labels are fully incorporated into the micellar structures, because the uptake of free oleate by the micelles is significantly faster (with a correlation time <10 −9 s) as compared to the release of oleate from the micelles into the bulk solution (with a correlation time >10 −4 s) (Fukuda et al, 2001). Fast surfactant diffusion from water into micelles implies that the water exchange into and out of the micelles is even faster, with lipid to water association lifetimes of the order of <100 ps (McCarney et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…ESR spectra of the spin-labeled oleic acid/sodium oleate system with lipophilic spin labels, characterized by anisotropic motions were simulated with the program "Chili" (Stoll and Schweiger, 2006). The spectra of ASL (the water soluble spin label) characterized by fast isotropic motion were simulated with "Garlic" of the EasySpin 3.1.1. software package (Stoll and Schweiger, 2006;McCarney et al, 2008). Best fit of the spectra was obtained by the least-square fitting method.…”
Section: Cw-esr Measurementsmentioning
confidence: 99%
“…For 0.35 T, experimental enhancements of up to À140 have been reported by Höfer et al [21]. A novel assortment of experiments that uniquely and sensitively probe the internal water dynamics of lipids, proteins and coacervates in the 0.1-0.5 ns correlation timescale has been successfully carried out at 0.35 T [20,[27][28][29]. Further explanation of this time scale is provided in Section 2.…”
Section: Introductionmentioning
confidence: 79%